Children's gender and parental educational strategies in rural and urban China: the moderating roles of sibship size and family resources. Issue 3 (26th May 2020) - Liu, Yixiao; Jiang, Quanbao; Chen, Feinian
Abstract: Despite the declining gender gap in education is consistently documented at the national level in China, little is known about the gendered pattern in education at the household level. This study aims at understanding the micro mechanism of current gendered pattern in educational attainment by examining parental educational strategies in Chinese families, where daughters are historically unprivileged, while children's education is highly valued. Using the first-wave data from China Education Panel Survey (CEPS, academic year 2013–2014), we examined the gender differences in family educational strategies measured as parental college expectation and children's private tutoring among junior high school students (aged 12–18, n  = 15, 733). The results show that daughters are more advantageous in parental educational strategies. Overall, daughters are more likely to be expected to attend college and enrolled in private tutoring, compared to sons. However, further analysis show that school performance explains daughters' advantages in parental college expectation and that their advantages (in both parental college expectation and private tutoring) vary with sibship size and family resources.